2015
DOI: 10.3109/10520295.2015.1077393
|View full text |Cite
|
Sign up to set email alerts
|

Altered serum and salivary C-reactive protein levels in patients with oral premalignant lesions and oral squamous cell carcinoma

Abstract: Chronic inflammation is associated with cancer development. C-reactive protein (CRP), an acute phase protein synthesized primarily in the liver, is a marker for inflammation and for the progression of many cancers. We compared serum and salivary CRP levels in 20 normal individuals, 20 patients with oral premalignant lesions and 20 patients with oral squamous cell carcinoma (OSCC) to assess its efficacy as a prognostic indicator for OSCC. Saliva and blood samples were obtained and evaluated for CRP levels. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The mean CRP level was 5.59±9.86 mg/l in group II and 31.72±31.01 mg/l in group III; the difference between the two groups was statistically significant (P<0.001). These results were similar to the findings of a study conducted by Metgud and Bajaj [22] who revealed that mean CRP levels were higher in patients with premalignant oral lesions compared to the controls. CRP levels in OSCC patients were elevated and were associated with advanced tumor stages [22].…”
Section: Discussionsupporting
confidence: 92%
“…The mean CRP level was 5.59±9.86 mg/l in group II and 31.72±31.01 mg/l in group III; the difference between the two groups was statistically significant (P<0.001). These results were similar to the findings of a study conducted by Metgud and Bajaj [22] who revealed that mean CRP levels were higher in patients with premalignant oral lesions compared to the controls. CRP levels in OSCC patients were elevated and were associated with advanced tumor stages [22].…”
Section: Discussionsupporting
confidence: 92%
“…CRP levels showed a graded increase according to the severity of the tumour. They suggested that CRP could be regarded as a prognosis marker in OSCC [ 53 ]. Khandavilli et al highlighted that the elevated level of preoperative CRP is an unfavourable prognostic indicator [ 54 ].…”
Section: Markers Of Inflammation In Osccmentioning
confidence: 99%
“…Some studies have reported an increase in CRP levels in patients with OSCC and have shown high CRP levels in OSCC patients linked to the advanced tumor stages (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%